Pathologic complete response after laparoscopic surgery following treatment with nivolumab and ipilimumab for anticancer drug-resistant MSI-high descending colon cancer: a case report and literature review - Hiroshi Sawayama; Yuji Miyamoto; Katsuhiro Ogawa; Mayuko Ohuchi; Yuki Hisano; Moeko Kato; Hiroki Tubakihara; Naoya Yoshida; Hideo Baba (Surgical Case Reports)
Abstract Background Preoperative treatment is performed for locally advanced colon cancer with extensive tumor proximity or suspected invasion of skeletal muscles, major organs, and blood vessels. Oxaliplatin-based regimens are often used in preoperative chemotherapy. However, microsatellite instability (MSI)-high colorectal cancer is often resistant to cytotoxic anticancer agents. Herein, we describe a case of treatment of anticancer drug-resistant MSI-high locally advanced colon cancer and review cases of complete response to immune checkpoint inhibitor therapy for colorectal cancer. Case presentation A 57-year-old woman was referred to our hospital with a large tumor in the descending colon and extensive thoracic and abdominal wall involvement, including the ribs and diaphragm. No distant metastasis was observed. The tumor had perforated the abdominal wall and formed an abscess. Upon visiting our hospital, emergency surgery was performed. An abdominal wall incision was made to drain the abscess and laparoscopic colostomy was performed. Histopathological examination of biopsy specimens revealed an adenocarcinoma with positive immunohistochemical expressions of both CDX2 and CK20. The patient was diagnosed with a descending colon cancer. Genetic examination found MSI-high, Kras mutation (F12G), and wild-type BRAF. After the inflammation improved, chemotherapy with the FOLFIRI regimen was initiated, but the tumor grew rapidly. As a second-line treatment, nivolumab and ipilimumab combination therapy was initiated. After four cycles of these therapies, the patient was administered nivolumab alone for five cycles. Tumor shrinkage was observed and radical surgery was performed. The patient underwent laparoscopic descending colon and partial thoracic and abdominal wall resection. The abdominal wall muscle was dissected from the abdominal cavity, and subcutaneous tissues, diaphragm, ribs were dissected from the body surface. Pathological examination revealed mucus components, fibrous tissues, and no malignant cells, indicating a complete pathological response (pCR). The patient had a good postoperative course and returned to work after being discharged. No recurrence was observed six months postoperatively. Conclusions Herein, we report a case of anticancer drug-resistant MSI-high colon cancer that was resected after treatment with immune checkpoint inhibitors, and a pCR was achieved. This new treatment strategy can be used for the treatment of cases that are not responsive to conventional therapies.